Effectiveness of Antimicrobial Stewardship Program in Long-Term Care: A Five-Year Prospective Single-Center Study - Alawi, Maha Mahmoud; Tashkandi, Wail A; Basheikh, Mohamed A; Warshan, Faten M; Ghobara, Hazem Ahmed; Ramos, Rosemarie B.; Guiriba, Mary Leilani; Ayob, Omar; Janah, Safiah Saad; Sindi, Anees Ahmad; Abdulhamid Ahmed, Suheib Ali; Dammnan, Salah; et al. (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Objective. To report the effectiveness of the antimicrobial stewardship program (ASP) in a long-term care (LTC) facility, by analyzing the change in antimicrobial consumption and cost and multidrug resistance (MDR) rates over a 5-year period. Method. A prospective interventional study was conducted at a 106-bed facility (nursing home: 100 beds and an intensive care unit (ICU): 6 beds). The ASP was designed and led by a multidisciplinary team including an infectious disease consultant, two clinical pharmacists, a clinical microbiologist, and an infection control preventionist. Five key performance indicators were monitored: (1) intravenous (IV)-to-oral switch rate, (2) consumption of restricted IV antimicrobials (raw consumption and defined daily doses (DDD) index), (3) cost of restricted IV antimicrobials, (4) antimicrobial sensitivity profiles, and (5) MDR rate among hospital-acquired infections (MDR-HAI). Result. A ∼5.5-fold enhancement of the IV-to-oral switch and a 40% reduction in the overall consumption of restricted IV antimicrobials were observed. Regarding the cost, the cumulative cost saving was estimated as 5.64 million SAR (US$1.50 million). Microbiologically, no significant change in antimicrobial sensitivity profiles was observed; however, a large-size reduction in the MDR-HAI rate was observed, notably in ICU where it declined from 3.22 per 1,000 patient days, in 2015, to 1.14 per 1,000 patient days in 2020. Interestingly, the yearly overall MDR rate was strongly correlated with the level of antimicrobial consumption. Conclusion. The implementation of a multidisciplinary ASP in LTC facilities should be further encouraged, with emphasis on physicians’ education and active involvement to enhance the success of the strategy.